1996
DOI: 10.1183/09031936.96.09122531
|View full text |Cite
|
Sign up to set email alerts
|

L-NAME aggravates pulmonary oxygen toxicity in rats

Abstract: L L--N NA AM ME E a ag gg gr ra av va at te es s p pu ul lm mo on na ar ry y o ox xy yg ge en n t to ox xi ic ci it ty y i in n r ra at ts s G. Capellier*, V. Maupoil**, A. Boillot + , J-P. Kantelip ++ , L. Rochette ‡ , J. Regnard ‡ ‡ , F. Barale* + L-NAME aggravates pulmonary oxygen toxicity in rats. G. Capellier, V. Maupoil, A. Boillot, J-P. Kantelip, L. Rochette, J. Regnard, F. Barale. ERS Journals Ltd 1996. ABSTRACT: Exposure to high oxygen concentration leads to acute lung injury and death in rats after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
13
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 31 publications
2
13
0
Order By: Relevance
“…We found that the treatment with L‐NAME of newborn rats reduced lung oedema. This is similar to the experiments with adult rats exposed to hyperoxia that showed that inhibition of NOS decreased water content in lungs (Capellier et al , 1996). The treatment of rat pups with L‐NAME also led to reduction of hyperoxia‐induced epithelial proliferation.…”
Section: Discussionsupporting
confidence: 89%
“…We found that the treatment with L‐NAME of newborn rats reduced lung oedema. This is similar to the experiments with adult rats exposed to hyperoxia that showed that inhibition of NOS decreased water content in lungs (Capellier et al , 1996). The treatment of rat pups with L‐NAME also led to reduction of hyperoxia‐induced epithelial proliferation.…”
Section: Discussionsupporting
confidence: 89%
“…significantly attenuated the O 2 -mediated injury to lung endothelium and alveolar epithelium in rats exposed to 60 h of hyperoxia (Mcelroy et al, 1997). Similarly, L-NAME increased the mortality rate in rats exposed to 60 h of hyperoxia from 22% (saline controls) to 57% (Capellier et al, 1996). These studies support the view that ambient O 2 environment plays a critical role in the response to NO synthase inhibition.…”
Section: Discussionsupporting
confidence: 74%
“…Adult rats exposed to hyperoxia, in the presence of L-NAME (nonspecific NOS inhibitor) and aminoguanidine (specific NOS2 inhibitor), had significantly increased mortality and HALI (32,33). In 6-to 8-week-old mice (FVBN strain), hyperoxia exposure did not impact on NOS2 expression or activity, but decreased NOS3 activity (6).…”
Section: Discussionmentioning
confidence: 99%